Knowledge of green computing among university students and lecturers in Malaysia - Bello, Abdullahi; Tunku Ahmad, Tunku Badariah (2013)
This is a conference paper presented in Singapore. The paper talked about the importance of students and lecturers having knowledge about green computing, which refers to energy-efficient and responsible use of computers and their associated subsystems. 180 students and 60 lecturers were surveyed. The results show limited and no knowledge of green computing among students and lecturers generally, with the exception of those coming from the ICT background. Implications on training in green computing are discussed.